The effect of eight-week shoulder girdle, pelvic girdle and combined corrective exercises on maximal voluntary ventilation in female students with upper crossed syndrome: a randomized clinical trial - Mansoureh Mogharrabi-Manzari; Golamali Ghasemi; Hossein Negahban (Shiraz University of Medical Sciences, 2021)
Background: The purpose of this study was to compare the effect of eight-week shoulder girdle, pelvic girdle and combined corrective exercises on maximal voluntary ventilation in female students with upper crossed syndrome. Methods: In this experimental randomized clinical trial, 45 female college students with upper crossed syndrome voluntarily participated and were randomly divided into three equal subgroups including shoulder girdle group, pelvic girdle group and combined group. The three groups performed corrective exercises of eight weeks and three times per week. The maximal voluntary ventilation was assessed before and after intervention. Results: The results showed that the main effect of group was significant (P = 0.029). The Least Significant Difference (LSD) post-hoc test demonstrated significant differences between combined groups with shoulder girdle group (P = 0.048) and pelvic girdle group (P = 0.011), but no significant differences between shoulder and pelvic groups (P = 0.537). The results showed a greater maximal voluntary ventilation in the combined exercise group than in the other groups. The main effect of time was significant for the three groups (P = 0.000). There was a significant interaction of groups by time for outcome measurement (P = 0.000). Conclusion: The results of this study provided preliminary guidance for the use of the comprehensive corrective exercises for simultaneous correction of anomalies.